Facial Expression of Emotions Through Facial Impressions In Animated Characters: Exploring the Visual Language of Emotional Expression in Animation (Journal of Advances and Scholarly Researches in Allied Education, 2011)
The challenge of communicating emotional content to an audience via animated characters has existed since the art form first appeared. As animation techniques and technology have advanced, animators and character designers find themselves with a multitude of resources and tools for the creation of facial expressions so as to effectively communicate the emotions of their animated characters within each scene.